2005
DOI: 10.1021/je050104v
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Phase Behavior of Triblock Copolymer + Salt + Water Two-Phase Systems at Different Temperatures and pH

Abstract: Data on phase equilibrium of aqueous two-phase systems formed by mixture of triblock copolymer, potassium phosphate, and water were measured as a function of three temperatures (283.15 K, 298.15 K, and 313.15 K), two pH values (7 and 12), and two copolymer molar masses (L35 of 1900 g mol -1 and F68 of 8400 g mol -1 ). The effect of the temperature was more pronounced on the behavior of the ATPS formed by the L35 copolymer as compared with that induced by the F68 copolymer. Temperature variation affected more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The system formed by PEG 8000 presents higher biphasic region, decreasing the region when PEG 4000 is used and even more when PEG 1500 is applied. This result is coherent with literature [19] [20].…”
Section: Partition Process Analysissupporting
confidence: 93%
“…The system formed by PEG 8000 presents higher biphasic region, decreasing the region when PEG 4000 is used and even more when PEG 1500 is applied. This result is coherent with literature [19] [20].…”
Section: Partition Process Analysissupporting
confidence: 93%
“…A buffer composed of K 2 HPO 4 and C 6 H 8 O 7 was selected to prepare ABS at controlled pH, within a range from 3 to 8. Although Pluronic-based ABS have already been studied at distinct pH values (e.g., K 2 HPO 4 /KH 2 PO 4 at pH 7 and K 2 HPO 4 /KOH at pH 12), , the pH window previously available was quite narrow, limiting the purification/fractionation of biomolecules. The buffer here used affords a wider pH range and also offers a more benign nature due to the presence of the natural organic acid C 6 H 8 O 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of (EO) x -(PO) y -(EO) x copolymers in ABS is not new, and their combination with conventional salts to induce liquid–liquid demixing in aqueous solution is well documented. Their phase separation phenomena were systematically studied considering distinct salts and Pluronics (varying both the molecular weight and EO/PO ratios) at distinct temperatures and pH. Scarcer are the studies evaluating the possibility of creating ABS composed of Pluronics and other polymers (e.g., dextran). , Foreseeing their future application, some authors unveiled the extraction aptitude of Pluronic-based ABS for metallic ions, , peptides/proteins, ,, and vitamins, as well as their use for the extractive transformation of steroids . Liu et al reported the combined use of copolymers and cholinium-based ILs, focusing on the liquid–liquid equilibrium data and the impact of the copolymer nature on the ABS formation.…”
Section: Introductionmentioning
confidence: 99%
“…18−24 Ease of use, low costs, shorter time for phase splitting, and recycling of the system components are advantages of the technique which makes it a suitable method to extraction. 25,26 Aqueous two phase systems are composed of two immiscible aqueous phases at a certain concentration which are in equilibrium. When a clear interfacial boundary formed between the two phases, the separation is done where one phase is rich and the other phase is poor in solute.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are different technologies to remove the phenol derivates such as advance and electrochemical oxidation, , reverse osmosis, membrane separation and filtration, , chemical coagulation, biological degradation, and adsorption. However, there are many problems that need to be considered before the mentioned methods can be exerted in reality, such as preserving organism activity, regenerating the adsorbents, decreasing the consuming energy, increasing the removal efficiency, and so on. Among these methods, aqueous two-phase system (ATPS) can be a noteworthy replacement to other separation methods because of its economically lasting and environmentally secure properties. Ease of use, low costs, shorter time for phase splitting, and recycling of the system components are advantages of the technique which makes it a suitable method to extraction. , Aqueous two phase systems are composed of two immiscible aqueous phases at a certain concentration which are in equilibrium. When a clear interfacial boundary formed between the two phases, the separation is done where one phase is rich and the other phase is poor in solute. …”
Section: Introductionmentioning
confidence: 99%